Identifikasi Kualitas Produk Gula Semut dan Gula Cair Nira Aren dengan Penambahan Pengawet Ekstrak Kulit Mangrove dan Kayu Nangka - -, Zulkahfi; Nurfadilla; Petra Kirana; Lusiana; Hidayat, M. Fitrah; Marson; Adilah (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2025)
Aren is one of the non-timber forest product commodities with various uses, ranging from palm sugar products to bioethanol. Palm juice has a short shelf life and will form alcohol groups that can affect product quality. The addition of preservatives is a solution that can be done to overcome this problem. This study aims to detect the characteristics and quality of granular and liquid palm sugar with the addition of natural preservatives. The results showed that there were variations in the color of the results based on preservatives where the addition of jackfruit wood extract was the best result with a light brown color on the sugar. The dominant flavor produced has a sweet taste (normal) in most of the treatments given. The quality of sugar produced showed a sugar content value of 100 brix in all treatments and types of preservative additions. The lowest water content was produced in the type of ant sugar using jackfruit wood extract around 0.69%. The average pH of all palm sugar products was acidic.